Determinants of Corporate Pay-out Policy and the Moderating Effects of Firm's Growth: Evidence From Pakistan - Hussain , Haroon; Md-Rus, Rohani; Al-Jaifi, Hamdan Amer; Hussain, Rana Yassir (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
This study investigates the determinants of dividend pay-out of listed firms in Pakistan from the year 2011 to 2015. The focus of the study is the life cycle theory of dividends, agency theory and signaling theory. Corporate governance indicators, firm efficiency and cash flow volatility are the main determinants used in this study. This study also includes eight corporate governance indicators namely insider ownership, ownership concentration, institutional ownership, board independence, board size, CEO duality, audit committee independence and remuneration committee. It is found that ownership concentration, institutional ownership, CEO duality, firm efficiency and cash flow volatility are the significant determinants of dividend pay-out in Pakistan. It is also found that growth opportunities significantly moderate the impact of ownership concentration, institutional ownership, CEO duality, firm efficiency, cash flow volatility on the dividend pay-out. This research is among the pioneer studies which examine the impact of firm efficiency on dividend pay-out. Likewise, the study is among the first attempts to incorporate growth opportunities as moderating variable in the relationship between corporate governance indicators, firm efficiency and cash flow volatility with dividend pay-out. Results show that the management of an efficient firm pays a high dividend to increase its reputation in the market. Furthermore, the negative signaling effect of dividend omission may not exist for efficient firms. It implies that efficient firms at their growth stage may also skip dividends.